Benchmarking Survey of Barangay Baay: A Basis for Extension Program - Jessie Ian Paragas; Gerald Perado; Jessie Paragas (Southeast Asian Journal of Science and Technology, 2018)
This paper is a benchmark survey designed to determine linguistic problems and needs of Barangay Baay in the town of Lingayen, Pangasinan, Philippines. It is hoped that through this paper, the Bachelor of Arts in English Language (ABEL) program of the Pangasinan State University shall set up an extension program in which the expertise of the faculty shall be utilized, the students shall be trained, and the target clientele shall be serviced. The paper’s descriptive research design has a total of 35 respondents composed of 28 males and 7 females who served the community either as elected barangay officials or appointed officers. The survey of needs shows that the respondents acknowledge some prevalent linguistic problems that affect the quality of their service to the community.  Some of their prevalent linguistic problems relate to their comprehension of materials that they read and listen to, to their limited skills in speaking especially in official capacity, and to their weakness in writing officials documents of the barangay. The paper recommends that the ABEL program of Pangasinan State University reach out to the respondents and address their needs.